ANALISIS KESULITAN MAHASISWA DALAM MENYELESAIKAN SOAL PEMECAHAN MASALAH PADA MATA KULIAH ALJABAR DAN TRIGONOMETRI - Imelda Imelda (Universitas Islam Sumatera Utara, 2018)
Abstract. The purpose of this study was to describe students' difficulties in solving problem solving problems in Algebra and Trigonometry courses. Subjects in this study were students of the Mathematics Education Faculty of Unika Santo Thomas Faculty of Teaching and Education study program in North Sumatra in semester 1 of the 2017-2018 school year, totaling 10 people. The data collection tool used in this study was a test of 5 questions in the form of a description. This type of research is a qualitative descriptive study. Data collection techniques are carried out by tests, observation, interviews and documentation. Data analysis techniques were carried out with the stages of data reduction, data presentation and conclusion drawing. The results showed that students had difficulty using the concept of equality and inequality squared, the use of the concepts of trigonometric formulas. Students also have difficulties in using number sequence principles and completing trigonometric equation solving, difficulties in disclosing information from problem solving and calculation errors. The contributing factor is the existence of several concepts and principles of algebra and trigonometry that are used in solving problems that have not been well controlled by students and are less thorough in performing calculations.Keywords: Analysis of Learning Difficulties, Algebra and Trigonometry